PENERAPAN MODEL BRAIN BASED LEARNING (BBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI USAHA DAUNN ENERGI - Utami Pemuji Lestari; Adam Malik; Diah Mulhayatiah (Journal of Teaching and Learning Physics, 2016)
According  to preliminary results Karya Pembangunan 2 Bandung, the average score test critical thinking skill of students lesson in physics are low, namely 44,80. One of alternatives that can be used in improved the skills of critical thinking students is by applying a  Brain Based Learning (BBL). Research aims to understand learning use the model BBL and the increase in critical thinking skill students to the matter effort  and energy. Methods used in this research is pre-experimental design, with the design one-group pretest-posttest .The sample is class XI MIA  which consisted of 25 people were chosen in using a technique sampling saturated. The results of the study showed the average all meeting activity teachers of 90,27 % and activity students 89,57 % are including the very good. In addition there has been increasing critical thinking skill students on effort matter and energy with a rise of 0,62 of medium category. Thus, Brain Based Learning’s model (BBL) can be used as alternatives in improved the skills of critical thinking of students to the matter effort and energy.